Development of a quality improvement audit tool for the primary care of children with chronic wet cough using a modified Delphi consensus approach. (24th September 2018) - Prime, Samantha J; Marchant, Julie; Chang, Anne B; Petsky, Helen L
Abstract : Aim: In the absence of quality indicators (QIs) for the management of chronic wet cough, our study's aim was to determine whether consensus on QIs reflecting good primary health care, prior to referral for children with chronic wet cough, can be achieved. Methods: A questionnaire consisting of 10 QIs was developed by a clinical working group based on current evidence and guidelines on the management of chronic wet cough in children. Each indicator reflected the quality of care provided to children with chronic wet cough in primary care prior to referral. A modified Delphi consensus questionnaire was undertaken involving expert paediatric respiratory clinicians and general paediatricians who graded the importance of each indicator for the purposes above. We a priori defined that consensus was considered achieved if >75% agreed on the indicator. Results: Twenty‐two specialists (from Brisbane, Melbourne, Perth and Canberra) participated in the survey. The cumulative number of years of their respiratory experience was 324 and that of general clinical practice was 504. Consensus was achieved in all 10 QIs, with 6 reaching 100% agreement. Mean agreement for the 10 items was 97%. Conclusion: As complete consensus was achieved on these QIs, it can be used as a provisional clinical audit tool and can guide the development of a robust audit tool for primary care clinical practice to assist with quality improvement initiatives.